Point-Of-Care Ultrasonography for Diagnosis of Medial Collateral Ligament Tears in Acute Knee Trauma; a Diagnostic Accuracy Study - Heydari, Farhad; Ahmadi, Omid; Golshani, Keihan; Derakhshan, Sirous (Archives of Academic Emergency Medicine, 2022)
Introduction: The use of point-of-care ultrasonography (POCUS) for identifying medial collateral ligament (MCL) tears has increased in recent years. This study aimed to evaluate the diagnostic accuracy of POCUS in the diagnosis of acute MCL tears of the knee. Methods: This prospective cross-sectional study was performed on patients with suspected MCL tear of the knee in the emergency department (ED). After history taking and primary physical examination, radiographic imaging of the knee was done. If there was no fracture in the knee X-ray, the POCUS examination was done. All of the patients were asked to refer to an orthopedic clinic, 7-10 days after discharge from ED, for Magnetic Resonance Imaging (MRI) evaluation. The second POCUS was done in the orthopedic clinic. Finally, the findings of POCUS and MRI were compared in diagnosing MCL injury. Results: Two hundred and fifty patients with a mean age of 25.05 ± 9.12 years were analyzed (86.8% male). According to the MRI findings, as the gold standard, 55(22.0%) patients had MCL injury. The sensitivity, specificity, positive and negative predictive values (PPV and NPV), and accuracy of ultrasound in detection of MCL injury, in comparison with MRI were 83.64 (95% CI, 71.20 to 92.23), 94.36% (95% CI, 90.13 to 97.15), 80.70% (95% CI, 69.95 to 88.25), 95.34% (95% CI, 91.83 to 97.38), and 92.00% (95% CI, 87.92 to 95.05), respectively. The area under the receiver operating characteristic (ROC) curve of POCUS was 0.890 (95% CI, 0.844 to 0.926). Conclusion: It seems that POCUS can be applied in screening patients with MCL tears following blunt knee trauma.